Ejercicio 2 Algebra
Ejercicio 2 Algebra
Ejercicio 2 Algebra
c) 2𝑥 + 𝑦 − 4𝑧 = −16
𝑥 − 2𝑦 + 6𝑧 = 21
2𝑥 + 3𝑦 − 5𝑧 = −23
(Paso 1)
2 1 −4 −16
(1 −2 6 | 21 )
2 3 −5 −23
(paso2)
2 1 −4 −16 1 1/2 −2 −8
(1 −2 6 | 21 ) F1=F1*1/2 → (1 −2 6 | 21 )F2=-1F1+ F2 →
2 3 −5 −23 2 3 −5 −23
1 1/2 −2 −8 1 1/2 −2 −8
(0 −5/2 8 | 29 ) F3= -2F1+F3 → (0 −5/2 8 | 29 )F2=-
2 3 −5 −23 0 −2 −1 −7
2/5*F2 →
1 1/2 −2 −8 1 1/2 −2 −8
(0 1 −16/5|−58/5)F3=-2F1+F3 → (0 1 −16/5|−58/5)F3*27/5
0 −2 −1 −7 0 0 27/5 81/5
→
1 1/2 −2 −8 1 1/2 −2 −8
(0 1 −16/5|−58/5)F2=16/5F1+F2→ (0 1 0 |−2)F1=2F3+F1→
0 0 1 3 0 0 1 3
1 1/2 0 −2 1 0 0 −1
(0 1 |
0 −2) F1=-1/2F2+F1→ ( 0 1 0|−2)
0 0 1 3 0 0 1 3
Obtenemos el resultado de las 3 incógnitas:
𝒙 = −𝟏
𝒚 = −𝟐
𝒛= 𝟑